Gênero social e religião: uma análise do discurso com base no Sistema de Avaliatividade - Alex Luis dos Santos (2018)
The variation, over time, of the places and functions historically associated with the feminine in society is possible and of interest for Discourse Analysis, insofar as new discourses - understood as "a dispersion of texts, whose historical mode of inscription allows defining as a space of enunciative regularities "(MAINGUENEAU, 2008, p.15) -, are produced and socialized among the members of a culture. If this production/socialization has to do with the linguistic element, it also articulates with history and with the institutions that provide the reason for the structures of meaning which it - history and institutions - manifest. In the context of institutions, ecclesiastical activity, whether instructing or discouraging, recommending or criticizing, through linguistic-discursive resources, is extremely relevant, since, as Bourdieu (2007, p.102) considers, the Church is still very active in our society. Based on this proposition, we define as a fundamental objective to discuss the relationship between social gender and religion, from the representations of the Catholic Church about the feminine in a set of texts published by the institution through the publisher Libreria Editrice Vaticana. For that, we assume methodologically the integrative procedure that aims to articulate the components of the discursive activity, apprehended in its dual social and textual dimension. In this work, the textual dimension is strongly influenced by the analytical categories of the Attitude of the Appraisal System, while the understanding of the social dimension is made possible by the dimensions of global semantics, capable of reporting both at the utterance level and at the enunciation level representations about the feminine in Christian-Catholic discourse. Among other things, it is possible to verify that the particular way in which the Catholic Church represents the woman in the discourse remains still quite inclined to maintain the order that privileges the man, but reveals a constitutive tension between this maintenance and the alteration. This denotes the historicity of representations and a process of social change within which women have gradually occupied different places and functions than they once did.